2015
DOI: 10.1159/000369209
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B Alleles B*15:01 and B*15:02: Opposite Association with Hepatitis C Virus Infection in Chinese Voluntary Blood Donors

Abstract: Background: Although human leukocyte antigens (HLA) have been shown in association with the outcomes of hepatitis C virus (HCV) infection among different ethnic groups, such studies remain absent in China, where the HCV prevalence is higher than the global average. Methods: In this study, 426 HCV-infected and 709 uninfected blood donors were analyzed, among whom the HLA alleles were sequenced using a high-resolution genotyping method. Results: At the 2-digit level, none of the alleles showed a statistical diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…In our previous study we have reported the association of HLA with HCV infection and spontaneous clearance in a cohort of Chinese blood donors . In this study, we further examined the association of KIR and KIR‐HLA with HCV spontaneous clearance in the context of IL28B polymorphism.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In our previous study we have reported the association of HLA with HCV infection and spontaneous clearance in a cohort of Chinese blood donors . In this study, we further examined the association of KIR and KIR‐HLA with HCV spontaneous clearance in the context of IL28B polymorphism.…”
Section: Discussionsupporting
confidence: 65%
“…However, few studies have evaluated differences in the native immune responses to infection between different populations. In this study, we aim to identify the role of KIR genes, genotypes, and KIR‐HLA on HCV spontaneous clearance in a cohort of HCV‐infected voluntary Chinese blood donors recruited in our previous studies …”
mentioning
confidence: 94%
“…HLA class I (A, B, C) and class II (DPB1, DQB1, DRB1) alleles were determined by polymerase chain reaction–sequencing based typing (PCR‐SBT) as previously described . In brief, genomic DNAs from each study subject were extracted from 1 mL whole blood in automated MagNA Pure LC 2.0 instrument (Roche Diagnostics, Indianapolis, IN) using MagNA Pure LC DNA Isolation Kit (Roche Diagnostics), following the manufacturer's instruction.…”
Section: Methodsmentioning
confidence: 99%
“…HLA class I (A, B, C) and class II (DPB1, DQB1, DRB1) alleles were determined by polymerase chain reaction-sequencing based typing (PCR-SBT) as previously described. 17,19 In brief, genomic DNAs from each study subject were extracted from 1 mL whole blood in The HLA alleles were assigned at a 4-digit level using the ASSIGN 3.5 software (Conexio Genomics, Perth, WA, Australia). Any ambiguous HUANG ET AL.…”
Section: Hla and Ifnl3 Snp Genotypingmentioning
confidence: 99%
“…This discrepancy implies a role of additional genetic risk factors in abacavir-related HSR. Apart from abacavir HSR, the presence of HLA-B * 57: 01 in HIV-infected patients has been implicated in slower disease progression, although the risk of progression may vary among patients carrying this allele, as also shown for HLA alleles in other viral infections, such as hepatitis C [28] . Further, a recent study of HLA-related mate choice implied its behavioral relevance in humans, with HLA similarity affecting different aspects of partnership [29] .…”
Section: Discussionmentioning
confidence: 96%